2010
DOI: 10.2298/jas1001079t
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of wheat production on family farms

Abstract: Serbian agricultural producers are currently facing a large number of challenges which have a significant influence on their business activities. Continuous monitoring and evaluation of existing family farms business activities is the only way to improve their profitability and enhance competitiveness in such conditions. Bearing this in mind, the objective of this research is to emphasize an importance of the economic analysis of wheat production on family farms and to contribute successfully to the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…Results reported in this paper show that in both wheat and sugar beet production, the variable cost had the share of more than 70% in the total costs. A similar cost distribution pattern was reported in wheat production [44]. Also, these authors reported a high share of fertilizer' cost in the wheat production costs.…”
Section: Economic Analysis Of the Sugar Beet And Wheat Productionsupporting
confidence: 79%
“…Results reported in this paper show that in both wheat and sugar beet production, the variable cost had the share of more than 70% in the total costs. A similar cost distribution pattern was reported in wheat production [44]. Also, these authors reported a high share of fertilizer' cost in the wheat production costs.…”
Section: Economic Analysis Of the Sugar Beet And Wheat Productionsupporting
confidence: 79%
“…Continuous monitoring and evaluation of the achieved results are necessary in order to improve the economic efficiency and profitability (Todorović and Filipović, 2010). The significance of the obtained results can be confirmed through dynamic analysis, which can be conducted in future research.…”
Section: Economic Indicators Of Honey Productionmentioning
confidence: 92%
“…Trend of average wheat yields, Republic of Serbia, period 1994 According to previous research (Todorović and Filipović, 2010), wheat is mostly produced on family farms. Results have shown that only farms with over 7.5 t ha -1 of yields make profits.…”
Section: Wheat For Seedmentioning
confidence: 99%